Fourth International Topical Meeting on High Temperature Reactor Technology, Volume 1 2008
DOI: 10.1115/htr2008-58175
|View full text |Cite
|
Sign up to set email alerts
|

Design Option of Heat Exchanger for the Next Generation Nuclear Plant

Abstract: The Next Generation Nuclear Plant (NGNP), a very High temperature Gas-Cooled Reactor (VHTR) concept, will provide the first demonstration of a closed-loop Brayton cycle at a commercial scale, producing a few hundred megawatts of power in the form of electricity and hydrogen. The power conversion unit (PCU) for the NGNP will take advantage of the significantly higher reactor outlet temperatures of the VHTRs to provide higher efficiencies than can be achieved with the current generation of light water reactors.B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Various conceptions of HTHEs are proposed and developed such as shell-and-tube heat exchangers [1][2][3][4], plate-fin heat exchangers [5,6], printed circuit heat exchangers [7][8][9], shell-and-plate micro heat exchangers [10][11] and bayonet tube heat exchangers [12][13]. The former three HTHEs are the potential IHXs for the HTGRs.…”
Section: Introductionmentioning
confidence: 99%
“…Various conceptions of HTHEs are proposed and developed such as shell-and-tube heat exchangers [1][2][3][4], plate-fin heat exchangers [5,6], printed circuit heat exchangers [7][8][9], shell-and-plate micro heat exchangers [10][11] and bayonet tube heat exchangers [12][13]. The former three HTHEs are the potential IHXs for the HTGRs.…”
Section: Introductionmentioning
confidence: 99%
“…1. Using the photochemical etching, the channel diameter is only 0.5-2.0 mm [1] and the compactness is up to 2500 m 2 /m 3 [7]. It was found that the volume of PCHE was 85% less than the traditional shell-and-tube heat exchanger under the same heat transfer rate and pressure drop conditions [10].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the special operating condition of VHTR, the intermediate heat exchanger should endure the ultra high temperature, high pressure and high pressure difference conditions [6]. The VHTR needs extensively large heat transfer areas to transfer heat due to the high heat flux in the core [7]. However, the efficiency of traditional shell-and-tube heat exchanger is too low to satisfy the requirements of small space [8].…”
Section: Introductionmentioning
confidence: 99%